Identification of a Novel Homozygous Missense (c.443A>T:p.N148I) Mutation in BBS2 in a Kashmiri Family with Bardet-Biedl Syndrome. (23rd February 2021) - Ali, Ghazanfar; Sadia,; Foo, Jia Nee; Nasir, Abdul; Chang, Chu-Hua; Chew, Elaine GuoYan; Latif, Zahid; Azeem, Zahid; Ain-ul-Batool, Syeda; Kazmi, Syed Akif Raza; Awan, Naheed Bashir; Khan, Abdul Hameed; et al.
Abstract : Background . Bardet-Biedl syndrome (BBS) is a rare autosomal recessive inherited disorder with distinctive clinical feature such as obesity, degeneration of retina, polydactyly, and renal abnormalities. The study was aimed at finding out the disease-causing variant/s in patients exhibiting clinical features of BBS. Methods . The identification of disease-causing variant was done by using whole exome sequencing on Illumina HiSeq 4000 platform involving the SeqCap EZ Exome v3 kit (Roche NimbleGen). The identified variant was further validated by Sanger sequencing. Results . WES revealed a novel homozygous missense mutation (NM_031885: c.443A>T:p.N148I) in exon 3 of the BBS2 gene. Sanger sequencing confirmed this variant as homozygous in both affected subjects and heterozygous in obligate parents, demonstrating autosomal recessive inheritance pattern. To the best of our knowledge, this variant was not present in literature and all publically available databases. The candidate variant is predicted to be pathogenic by a set of in-silico softwares. Conclusion . Clinical and genetic spectrum of BBS and BBS-like disorders is not completely defined in the Pakistani as well as in Kashmiri population. Therefore, more comprehensive genetic studies are required to gain insights into genotype-phenotype associations to facilitate carrier screening and genetic counseling of families with such disorders.